Assessment of Carotid Intima-Media Thickness as an Early Marker Of Vascular Damage In Hypertensive Children - Liz Andréa Villela Baroncini; Lucimary de Castro Sylvestre; Camila Varotto Baroncini; Roberto Pecoits Filho (Arquivos Brasileiros de Cardiologia)
Abstract Background: The increased carotid intima-media thickness (CIMT) correlates with the presence of atherosclerosis in adults and describes vascular abnormalities in both hypertensive children and adolescents. Objective: To assess CIMT as an early marker of atherosclerosis and vascular damage in hypertensive children and adolescents compared with non-hypertensive controls and to evaluate the influence of gender, age, and body mass index (BMI) on CIMT on each group. Methods: Observational cohort study. A total of 133 hypertensive subjects (male, n = 69; mean age, 10.5 ± 4 years) underwent carotid ultrasound exam for assessment of CIMT. One hundred and twenty-one non-hypertensive subjects (male, n = 64; mean age, 9.8 ± 4.1 years) were selected as controls for gender, age (± 1 year), and BMI (± 10%). Results: There were no significant difference regarding gender (p = 0.954) and age (p = 0.067) between groups. Hypertensive subjects had higher BMI when compared to control group (p = 0.004), although within the established range of 10%. Subjects in the hypertensive group had higher CIMT values when compared to control group (0.46 ± 0.05 versus 0.42 ± 0.05 mm, respectively, p < 0.001; one-way ANOVA). Carotid IMT values were not significantly influenced by gender, age, and BMI when analyzed in both groups separately (Student's t-test for independent samples). According to the adjusted determination coefficient (R²) only 11.7% of CIMT variations were accounted for by group variations, including age, gender, and BMI. Conclusions: Carotid intima-media thickness was higher in hypertensive children and adolescents when compared to the control group. The presence of hypertension increased CIMT regardless of age, gender, and BMI.